Satyagraha and South Africa - Renata Czekalska (Ksiegarnia Akademicka Publishing, 2021)
The article presents the results of research carried out mainly on Mahatma Gandhi’s written statements which the authors refer to both a historical and socio‑political background. It is the first part of the planned two‑part study on mutual relations between Mahatma Gandhi’s satyagraha and South Africa, therefore it is focused on the interdependencies between the origin of the idea and the place where it was invented. The authors seek to answer two main questions: 1) whether Gandhi has entered into a dialogue with the native people of South Africa, and 2) whether Gandhi’s idea of non‑violent fighting for social rights included the native population of South Africa. The study also presents an outline of the evolution of Gandhi’s attitudes towards Africans and the Coloured People.